Organizational Midline Study: Vaishali, Bihar State, India - Jagannath, Pratyaya; Raj; Nagpal, Mansi; Khatri-Chhetri, Arun (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
In 2011, CCAFS conducted a baseline study in India which included a household survey, a qualitative village study and an organizational survey at two CCAFS sites, i.e., Karnal district in Haryana and Vaishali district in Bihar. To measure the impact of the program, the BISA-CIMMYT conducted a midline study containing the same three components, i.e., Household Midline Surveys (HMS), Village Midline Surveys (VMS) and Organizational midline surveys (OMS). This report summarizes the findings from the Organisational Midline Survey (OMS) carried out in June 2019. CCAFS' organizational-level Midline studies supplement the quantitative household midline surveys and the qualitative village midline studies conducted at the same locations.